China's exports and the oil price - Jo\~ao Ricardo Faria; André Varella Mollick; Pedro H. Albuquerque; Miguel A. León-Ledesma (University of Kent, Department of Economics, 2008)
The increase in oil prices in recent years has occurred concurrently with a rapid expansion of Chinese exports in the world markets, despite China being an oil importing country. In this paper we develop a theoretical model that explains the positive correlation between Chinese exports and the oil price. The model shows that Chinese growth can lead to an increase in oil prices that has a stronger impact on its export competitors. This is due to the large labor force surplus of China. We then examine this hypothesis by estimating a reduced form equation for Chinese exports using Rodrik (2006)'s measure of export competitiveness, together with the oil price, productivity, real exchange rate, and foreign industrial production over the monthly 1992-2005 period. The results suggest a stable relationship and yields slightly positive values for the price of oil and elastic coefficients for export competitiveness, along with the expected negative elasticity for the real exchange rate.
Keywords: F14; F43; 330; China; oil prices; competitiveness; exports; productivity; Ölpreis; Export; Wechselkurs; Produktivität; Wettbewerb; China